Principles of risk management and insurance - Rejda, George E., 1931- (Boston : Pearson/Addison Wesley, 2008)
This book provides complete and current treatment of major risk management, functional and financial operations of insurers, legal principles, life and health insurance, property and liability insurance, employee benefits and social insurance.
Includes bibliographical references and index.
Keywords: Insurance; Risk (Insurance).; Risk management